A COMPARATIVE STUDY ON LEVEL OF COORDINATION BETWEEN MALE ATHLETE AND NON ATHLETE COLLEGE STUDENTS - Das, Arup (International Journal of Psychosocial Rehabilitation, 2024)
Coordination is a factor that is basic to performance and especially to highly complex movements (it may be defined as the ability of the performer to integrate types of movements in a specific pattern). We need coordination as we are to perform a lot of physical movements to accomplish the daily assignment. To get maximum output with minimum effort, i.e., economical movement, rhythmical movement, graceful and efficient movement, we need coordination. The purpose of the study was to compare the status of coordination between athlete and nonathlete male and female groups. Forty students were chosen from 4 different groups, which are athlete male, nonathlete male, athlete female, and nonathlete female, from the Department of Physical Education at Kandra College within the age group of 18 to 21 years. Coordination was analyzed by a specific test for coordination referred to by the Barrow Motor Ability Test (1983). The result revealed that both male and female athletes have a greater level of coordination than male nonathletes and nonathletes, and both male and nonmale athletes have a greater level of coordination than both female athletes & female nonathletes.